Peningkatan Pemahaman Konseptual Siswa melalui Strategi Pembelajaran Deep Learning - Fitria Carli Wiseza; Ibermarza Ibermarza (Edu Happiness: Jurnal Ilmiah Perkembangan Anak Usia Dini, 2025)
This study aims to analyse the effectiveness of implementing deep learning strategies in improving primary school students' conceptual understanding of Natural and Social Sciences (IPAS), particularly the material ‘Weather Changes and Their Impacts’. The research approach used was Classroom Action Research (CAR) over two cycles, each consisting of planning, implementation, observation, and reflection stages. The research subjects were 22 fifth-grade students from Public Alementary Cchool (SDN) 144/II Pasir Putih Bungo, consisting of 10 boys and 12 girls. Data collection techniques included observation, evaluation tests, reflective interviews, and documentation. The results showed a significant increase in students' conceptual understanding after the application of in-depth learning strategies through problem-based learning activities, group discussions, phenomenon exploration, and independent reflection. The average score for student understanding increased from 36.5 (pre-cycle) with a criterion of poor to 64% with a criterion of good (cycle I) and 91 with a criterion of very good (cycle II) with a criterion of very good. Deep learning has been proven to build students' critical thinking skills, knowledge transfer abilities, and ecological awareness related to weather change phenomena and their impacts. Thus, this strategy is suitable for application in Natural and Social Sciences (IPAS) learning at the primary school level to develop meaningful, reflective, and contextual learning.